Figural Creativity Test: Initial Investigation for Use in Adolescents and Adults - Tatiana de Cassia Nakano; Laís Rovina Batagin; Luana Hillary Fusaro (Paidéia (Ribeirão Preto), 2022)
Abstract As part of an investigation into the psychometric qualities of the Children’s Figural Creativity Test (TCFI) for adolescents and adults, the research examined factor analysis, precision, and influence of gender and educational level variables. The sample consisted of 309 individuals (M = 33.35 years; SD = 22.04), 166 females and three levels of education, who filled out the aforementioned instrument. During the exploratory factor analysis, four factors were identified: the elaboration factor (F1), the external aspects factor (F2), cognitive aspects factor (F3), and emotional aspects factor (F4). Precision of the instrument was ω = 0.776. We found differences in F1 and total score favoring females, in all factors and in total creativity, favoring the group with the highest education. Prior to using the instrument with individuals older than those considered in the children’s version of the test, studies investigating other psychometric characteristics are advised.